Pengembangan Media Audio Visual Panduan Praktis Pola Hidup Sehat bagi Lansia - Lutfi Wibawa; - Hiryanto; Eko Budi Prasetyo (LPPM UNY, 2014)
This research resulted in a audio-visual media such as compact discs (CDs) practical guide healthy lifestyle for the elderly and lecture modules on S1 majoring in School Education in Adult Education courses. The development research conducted in Yogyakarta with the target groups of elderly who are members of the elderly community. In this study, data were collected by using group forum discution, in-depth interviews, documentation and observation. Data were analyzed using qualitative analysis techniques. Research and development is carried out in two years, the irst year has produced a practical guide CD healthy lifestyles for seniors who already validated in a limited and lecture modules on S1 Department of School Education in Adult Education courses